Nomads, Empires, States Modes of Foreign Relations and Political Economy, Volume I - van der Pijl, Kees (Pluto Press, 2007)
This book breaks new ground in the way we think about international relations theory.Kees van der Pijl argues that by making the "nation-state" the focus of international relations, the discipline has become Euro-centric and a-historical. Theories of imperialism and historic civilisations, and their relation to world order, have been discarded. With more than half the world's population living in cities, with unprecedented levels of migration, global politics is present on every street corner. The "international" is no longer only a balance of power among states, but includes tribal relations making a comeback in various ways. Outlining a new approach to IR theory, the book makes a case for a re-reading of world history in terms of foreign relations, and shows what it reveals about both our past and our future.